The causal relationship between energy consumption and economic growth in the ASEAN-5 countries - Azam, Muhammad; Khan, Abdul Qayyum; Bakhtyar, Bardia; Emirullah, Chandra (Elsevier B.V., 2015)
The objective of this study is to examine the causal relationship between energy consumption and economic growth for ASEAN-5 countries which includes Indonesia, Malaysia, Thailand, Singapore, and the Philippines.For empirical examination annual time series data in the period of 1980-2012 are used.The results of Johansen co-integration test reveal that there exists one co-integrating relationship among the variables in case of Indonesia, Malaysia, the Philippines and Singapore. The results uncover the existence of two co-integrating associations among the variables for Thailand.The Granger causality test suggests that there is no unilateral causality for Indonesia as in all the three cases. In case of Malaysia the economic growth caused energy consumption, however, no evidence is found for causality either from exports or from gross fixed capital formation to energy consumption. While, in the cases of Thailand and the Philippines the direction of causality runs from gross fixed capital formation to energy consumption. For Singapore, energy consumption runs from two sides i.e. one from exports side and the other from gross fixed capital formation side. The findings exhibit that energy consumption has significant and long run relationship to economic growth for almost all ASEAN-5 countries.The findings suggest that policy makers need to formulate policies conducive to the energy development which will consequently accelerate sustainable economic growth in ASEAN countries. Energy development should be based on the existing condition of each country.A comprehensive investment framework for renewable energy should also be developed besides maintaining adequate energy inventory.The ASEAN countries should strengthen their institutions and capacity as well as cooperation in energy management and development.